Respuesta :
12b - 4 = 12 + 2(b+1)
2 × b = 2b
2 × 1 = 2
12b - 4 = 12 + 2b + 2
+ 4 +4
12b = 12 + 2b + 2 + 4
-2b -2b
10b = 12 + 2 + 4
10b = 18
÷10 ÷ 10
b = 1.8
There you go! I really hope this helped, if there’s anything just let me know! ☻
2 × b = 2b
2 × 1 = 2
12b - 4 = 12 + 2b + 2
+ 4 +4
12b = 12 + 2b + 2 + 4
-2b -2b
10b = 12 + 2 + 4
10b = 18
÷10 ÷ 10
b = 1.8
There you go! I really hope this helped, if there’s anything just let me know! ☻
12b - 4 = 12 + 2(b + 1)
12b - 4 = 12 + 2b +2
12b - 4 = 14 + 2b
+ 4 =+ 4
12b = 18 + 2b
-2b = -2b
10b = 18
----- = ----
10 10
b = 1.8
answer: 1.8